2021
DOI: 10.3168/jdsc.2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of route of administration of dinoprost tromethamine on plasma profiles of 13,14-dihydro-15-keto-prostaglandin F2α and progesterone in lactating Holstein cows

Abstract: Our objective was to determine the effect of route of administration of dinoprost tromethamine 7 d after treatment with GnRH on circulating 13,14-dihydro-15-keto-prostaglandin F2α (PGFM) and progesterone (P4) concentrations in lactating dairy cows. Multiparous Holstein cows fitted with indwelling jugular catheters were randomized 7 d after the last GnRH of an Ovsynch protocol (G2, d 0) to receive 25 mg of dinoprost tromethamine either intramuscularly (IM) or subcutaneously (SC). The SC cows had greater circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Quality assurance of beef in particular seeks to minimize meat damage to preserve its value, by minimizing the use of hormones in beef production (40). The previous studies of Chebel et al (50) and Mezera et al (51), which focused on differences between SC and IM administration, indicated no differences in cows that underwent complete luteolysis. These authors suggested that the SC method of dinoprost administration is acceptable for CL regression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Quality assurance of beef in particular seeks to minimize meat damage to preserve its value, by minimizing the use of hormones in beef production (40). The previous studies of Chebel et al (50) and Mezera et al (51), which focused on differences between SC and IM administration, indicated no differences in cows that underwent complete luteolysis. These authors suggested that the SC method of dinoprost administration is acceptable for CL regression.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the estrous cycle is widely applied in veterinary practice for estrus synchronization. The most effective routes and sites for administration of PGF 2α analogs, used for manipulation of the reproductive processes in breeding cows, have been the subject of numerous studies ( 40 , 50 , 51 ). Besides IM administration of PGF 2α analogs, their subcutaneous injection (SC) in the cervical area, or SC injection in the ischio-rectal fossa have also produced declines in P 4 concentration, inducing luteolysis in the cow ( 40 , 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations